2002
DOI: 10.1038/sj.ijir.3900795
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for combination therapy of intraurethral prostaglandin E1 and sildenafil in the salvage of erectile dysfunction patients desiring noninvasive therapy

Abstract: Corpus cavernosum smooth muscle relaxation and hence penile erection are regulated in part by increases in smooth muscle synthesis of the second messengers cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP). The object of this study was to determine 30-month follow-up results in motivated patients desiring noninvasive medical therapy using sildenafil citrate (Viagra) in combination with intraurethral prostaglandin E 1 (PGE 1 ) (Medicated Urethral System for Erection [MUSE]). Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 17 publications
3
29
0
3
Order By: Relevance
“…This perhaps points to additional variables involved in therapeutic compliance such as education level, socioeconomic status, medication costs and other psychosocial factors. In a case series of 28 patients, Nehra et al 13 achieved a 100% rate of erections deemed sufficient for penetration with combination treatment after patients failed sildenafil and/or alprostadil monotherapy. Using this regimen, no patients desired a transition to more invasive treatments such as ICI or penile prosthesis implantation.…”
Section: Pde5i Plus Intraurethral Alprostadilmentioning
confidence: 99%
“…This perhaps points to additional variables involved in therapeutic compliance such as education level, socioeconomic status, medication costs and other psychosocial factors. In a case series of 28 patients, Nehra et al 13 achieved a 100% rate of erections deemed sufficient for penetration with combination treatment after patients failed sildenafil and/or alprostadil monotherapy. Using this regimen, no patients desired a transition to more invasive treatments such as ICI or penile prosthesis implantation.…”
Section: Pde5i Plus Intraurethral Alprostadilmentioning
confidence: 99%
“…The proposed use of combination therapy will provide an alternative option for many patients who do not accept more invasive treatments such as VCD and intracavernosal injections. 12 Conclusions MUSE can provide good efficacy and compliance in up to 63% of patients. A mean SHIM score of Z16 stratified for a successful and long-term outcome with MUSE therapy.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, the combined use of IC 12 or intraurethral 10,11 PGE1 and the first effective oral PDE-5 inhibitor sildenafil taken together at the time of intercourse has been reported successful in many patients not responding to either single drug. The present data indicate that such a combination can also be effective when the drugs are administered quite separately.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 They include needle aversion, lack of spontaneity, partner rejection of the procedure, pain, and increased risks of priapism or fibrotic changes in the penis after prolonged use. [5][6][7][8][9] In patients not responding to either type of monotherapy, the combination of both has been tried in order to get additive or synergistic effects, which has been carried out by combining PGE1 delivered either transurethrally 10,11 or by IC injection (as triple agent, mixed with papaverine and phentolamine) 12 with the oral PDE-5 inhibitor sildenafil at 100 mg dose. These studies reported satisfactory results in many patients previously not responding to monotherapy with either drug.…”
Section: Introductionmentioning
confidence: 99%